The Effect of Space Holder Types and Composition on the Properties of Zirconia Foam - MUHAMMAD HADI BIN ASMURAD,; MAT NOOR, FAZIMAH; Azzura Ismail, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Ceramic foams can be classified as porous and brittle materials with pore formation inside. These materials have their own distinct physical properties that have been used for a variety of applications, including thermal insulation, filtration, and as a substrate for catalytic converters, which are frequently used to lower vehicle emissions. This project used the space holder method to create Zirconia foam, which involves adding and removing a space holder material from the mixture. Sodium chloride, sago starch, and tapioca starch were the three types of materials employed as the space holder material. Their weight percent compositions were 10%, 20%, and 30%, respectively. Distilled water was used to dissolve and remove the space holder components. While Polyethylene Glycol (PEG) and carboxymethyl cellulose (CMC) were utilised as binders which act as glue to boost the powder's green strength during the compaction process. All the mixed ingredients were compacted into a solid cylinder sample after being ball-milled. Following that, the samples were sintered in a furnace at 1400°C. Finally, the samples were tested and analyzed by doing the microstructural analysis, density and porosity testing, and shrinkage analysis. Based on the findings, the zirconia foam has been effectively created using the space holder method, and the differences in the composition of the space holder material do affect the qualities of the final product. As the tapioca starch was used as a space holder, the pores were closed. However, after the sodium chloride was used as a space holder, the pores were open and clear. Unfortunately, the sample with the sago starch as a space holder material was totally collapsed after sintering. It can be concluded that sodium chloride is the ideal material to utilise as a space holder since it can create samples with the least amount of shrinkage, the highest density, and the smallest amount of porosity when the optimal composition is used, which is 20% than tapioca starch and other composition.